Avaliação da função cardiopulmonar de pacientes sobreviventes à COVID-19 em reabilitação ambulatorial. - LIMA, Priscila Bezerra de (Universidade Federal do Oeste do Pará, 2023)
COVID-19 is a disease that broke out in late 2019 in China and became a pandemic in March 2020 to the present day. It is worrying that COVID-19 is a disease that mainly causes changes in the cardiorespiratory system with a deficit in respiratory muscle function and exercise tolerance, which can lead to long-term sequelae. Objective: to evaluate the cardiopulmonary function of patients surviving COVID-19 in outpatient rehabilitation in the city of Santarém. Material and Method: After approval by the Research Ethics Committee with human beings, an analytical-descriptive, longitudinal, prospective and quantitative study was carried out. The evaluation stages were: interview through a semi-structured questionnaire; spirometry; sixminute step test (6MDT), in addition to dyspnea (MRC), functional independence (FIM) and perceived exertion (Borg scale) scales. Statistical analyzes were performed using Microsoft Excel 2010 software and R software. Results and Discussion: The sample consisted of 30 post-COVID-19 patients who underwent outpatient physical therapy treatment. The male sex was prevalent (73%), the mean age was 53 ± 13 years, 60% had the disease in its severe form. Compensatedly controlled comorbidities were found not to be risk factors for disease severity. The clinical manifestation and relevance of a pathological condition can be heterogeneous: whether the hypertension was treated or not; whether the stage of chronic lung disease was only mild or very severe with low blood oxygen levels, there are confounding factors to consider. The first symptoms of the disease did not define nor were related to the hospitalization history, making the patient's stability during the disease unpredictable. Pulmonary involvement through chest tomography and the history of hospitalization generated a strong impact with the ventilatory support used, where the latter and the length of hospital stay were directly related to the severity of the disease. Spirometry as an evaluative criterion for outpatient rehabilitation showed restrictive disorders. The functionality scales showed a mild degree of MRC, cognitive alterations in category 6 of the FIM. When the 6MWD was evaluated, predictive variables showed that the decrease in 6MWD performance with advancing age is strongly associated, since there is a reduction in physical capacity with aging. Final considerations: In this research, it was considered that patients sought outpatient physical therapy treatment early, about 2 months after the first symptoms of COVID-19, but still had the persistence of debilitating symptoms, for an average period of 8 months. months after the onset of COVID-19, however with significant improvement in the morbidity stage of the disease, even after the use of ventilatory support in therapy (mainly non-invasive). It is essential to associate physical capacity tests with pulmonary function tests, in order to maintain the follow-up of patients, as well as measure the functional impact in the long term. Therefore, there is a need to welcome the survivors of the first waves, as the premise of the post-COVID-19 syndrome is increasingly strengthened.